Modulation of haemopoietic radiation response of mice by diclofenac in fractionated treatment - Hofer, M; Pospísil, M; Pipalová, I; Holá, J (Physiological research, 1996)
The effects of diclofenac, an inhibitor of prostaglandin synthesis, were studied on the acute radiation syndrome elicited in mice by fractional irradiation. Several haematological parameters were evaluated in mice irradiated with 5x2 Gy and 3x, 4x, or 5x3 Gy (intervals between fractions 24 h) from a 60Co gamma-ray source. The animals were treated with diclofenac either before each fraction or only once before the last fraction. The survival of mice was recorded after the irradiation regimen of 5x3 Gy followed by a "top-up" dose of 3.5 Gy given 24 h after the last radiation fraction. Statistically significant enhancement of the endogenous spleen colony formation and of leukopoiesis was found in mice treated with diclofenac repeatedly, as compared with both saline-treated irradiated controls and animals administered a single diclofenac dose, if a sublethal total radiation dose had been accumulated. However, following accumulation of a lethal total radiation dose, slightly impaired survival was observed in mice given diclofenac. It follows from the results that diclofenac is a suitable drug for enhancing leukopoiesis impaired by sublethal fractionated irradiation. Nevertheless, undesirable side effects of this drug negatively influence the survival of experimental animals following a lethal accumulated radiation dose.
Keywords: záření gama; Animals; Gamma Rays; Whole-Body Irradiation; Hematopoietic Stem Cells; diklofenak; analýza kolonii tvořících jednotek; Radiation Injuries, Experimental; počet leukocytů; Mice; myši; Colony-Forming Units Assay; Hematopoiesis; Leukocyte Count; Male; myši inbrední C57BL; Mice, Inbred CBA; experimentální radiační poranění; Diclofenac; hematopoetické kmenové buňky; hematopoéza; Cell Survival; zvířata; mužské pohlaví; viabilita buněk; myši inbrední CBA; Mice, Inbred C57BL; počet erytrocytů; celotělové ozáření; Erythrocyte Count